How Can Libraries Support Student Research? - Idris, Siti Hafsyah; Arifin, Ridwan; Prayitno, Heri (Knowledge Garden: International Journal of Library Studies, 2023)
Libraries have long been recognized as vital institutions for supporting student research endeavors across various educational levels. This study explores the multifaceted ways in which libraries can effectively bolster student research. Drawing from a comprehensive review of literature, surveys, interviews with librarians, and case studies of successful library programs, this research provides valuable insights into the role libraries play in enhancing the research skills and academic success of students. The findings underscore the importance of library resources, including access to scholarly databases, interlibrary loans, and research assistance, in facilitating students' information retrieval and literature review processes. Additionally, libraries' instructional programs and workshops are shown to empower students with research methodologies, information literacy, and critical thinking skills. Furthermore, this study delves into the evolving role of digital technologies and online resources in supporting student research, highlighting how libraries adapt to the changing landscape of information dissemination. Collaboration between librarians and faculty is also examined as a key factor in promoting research opportunities for students. In a rapidly evolving academic landscape, this research serves as a valuable resource for librarians, educators, and institutions seeking to optimize library services for the benefit of student researchers. By offering practical recommendations and best practices, it underscores the essential role libraries play in nurturing the next generation of scholars and fostering a culture of research excellence.